WELCOME THE ERA OF MODERN MADRASAH LEADERSHIP - Fahru Rijal; Anis Zohriah; Ahmad Qurtubi (Cakrawala Pedagogik, 2023)
In middle school management, the challenge of change can be implemented effectively if management and administration are managed properly. Various internal conflicts in the process of providing education usually arise due to bad management. This research is a qualitative research with a phenomenological approach. The study used subjects at MA Daar El-Ulum Saketi, Pandeglang Regency, Banten Province. The definition of a person takes into account competence, knowledge, experience and personal characteristics that can influence operational, organizational and public performance and leadership roles. Inter-industry activities which are also carried out with external components are the focus of the leadership in the process of realizing the vision and mission of the organization.